WETON DALAM PERSPEKTIF GENERASI Z; STUDI FENOMENOLOGI SISTEM PENANGGALAN JAWA DI DESA BETAO KEC. PITU RIAWA KAB. SIDRAP PERSPEKTIF ILMU FALAK - Margaretha, Indri; Irfan, Irfan (Universitas Islam Negeri Alauddin Makassar, 2026)
ABSTRACT Weton is a combination of days in the seven-day calendar (Sunday-Monday) with five Javanese market days (Legi, Pon, Wage, and Kliwon) to form a 35-day cycle. This main problem is then formulated into several sub-problems or research questions, namely: how the results of generation z interpret weton in everyday life and how the Javanese calendar system is related to the Islamic calendar system from the perspective of astronomy. This study aims to examine and analyze how generation z responds to weton and what its relationship is with astronomy. This type of research is a qualitative field research with the research approaches used are: phenomenological approach, and astronomy. The data sources in this study are based on the results of observations and interviews as well as documentation supported by document studies. Data processing and analysis techniques are carried out by data collection, data processing, and data presentation. The results of the study show first, that generation z does not all know about weton and only follows the traditions carried out by their parents as a form of respect. Second, the Javanese weton calendar system and the Islamic calendar have the same relationship discussing the determination of the beginning of the month. In determining each calendar, astronomy plays a crucial role in calculating the beginning of the month. The implication of this research is the need for cultural education to ensure that traditional heritage is not forgotten. Astronomy as an educational tool can be beneficial by providing examples of how to determine time with Islamic values while preserving culture.